Nanotoxicology and Nanosafety 2.0 - Wang, Ying-Jan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
With the rapid development of nanotechnology, nanomaterials have been widely applied in many industrial sectors, including medicine, consumer products, and electronics. While such technology has brought benefits and convenience to our daily lives, it may also potentially threaten human health. In some cases, nanomaterials present unexpected risks to both humans and the environment. Assessments of the potential hazards associated with nanotechnology have been emerging, but substantial challenges remain, because the large number of different nanomaterials cannot be effectively evaluated in a timely manner. The development of a good strategy for a nanomaterials hazard assessment not only promotes the more widespread adoption of non-rodent or 3Rs principles, but also makes nanotoxicology testing more ethical, relevant, and cost- and time-efficient. A thorough understanding of the mechanisms by which nanomaterials perturb biological systems is critical for a more comprehensive elucidation of their nanotoxicity, and this will also facilitate the development of prevention and intervention policies against adverse outcomes induced by them. We hope that the articles included in this eBook can provide updated knowledge on nanotoxicology and nanosafety, from the point of view of both toxicology and ecotoxicology.